Implementasi Pembelajaran Diferensiasi dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Ppkn di SMP Swasta Kristen BNKP Gunungsitoli - Harefa, Naftali Nofriaman; Lase, Berkat Persada; Harefa, Anugerah Tatema; Lase, Fatiani (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to determine the implementation of differentiated learning in increasing student interest in Civics subjects at BNKP Gunungsitoli Christian Private Junior High School, this research uses qualitative methods with a descriptive approach. The tools used by researchers in collecting data are recordings, pictures, and field notes. Based on the results of the research found that the implementation of differentiated learning in increasing students' interest in learning Civics Subjects at BNKP Gunungsitoli Christian Private Junior High School teachers make observations, interviews and give questionnaires to students to find out what the interests of students are in the classroom with teachers knowing students' learning interests, teachers use learning strategies, namely content differentiation that adjusts learning materials according to student interests. Process differentiation is a learning strategy that adjusts the way teachers deliver material or provide instructions to students, product differentiation is a teacher strategy in providing varied learning methods, and differentiation of the learning environment learning methods outside the classroom (outdoor). The impact of the implementation of differentiated learning has succeeded in increasing student interest in Civics subjects at BNKP Gunungsitoli Christian Private Junior High School. In addition, differentiated learning increases students' passion for learning the material, adds experience, provides actual examples, and learning is more fun so that students do not feel bored in learning.